A new chiral phenomenon of orientational chirality, its synthetic control and computational study - Jin, Shengzhou; Xu, Ting; Tang, Yao; Wang, Jia-Yin; Wang, Yu; Pan, Junyi; Zhang, Sai; Yuan, Qingkai; Rahman, Anis Ur; Aquino, Adelia J. A.; Lischka, Hans; Li, Guigen (Frontiers in Chemistry, 2023)
A new type of chirality, orientational chirality, consisting of a tetrahedron center and a remotely anchored blocker, has been discovered. The key structural element of this chirality is characterized by multiple orientations directed by a through-space functional group. The multi-step synthesis of orientational chiral targets was conducted by taking advantage of asymmetric nucleophilic addition, Suzuki-Miyaura cross-coupling and Sonogashira coupling. An unprecedented catalytic species showing a five-membered ring consisting of C(sp2)-Br-Pd-C(sp2) bonds was isolated during performing Suzuki-Miyaura cross-coupling. X-ray diffraction analysis confirmed the species structure and absolute configuration of chiral orientation products. Based on X-ray structures, a model was proposed for the new chirality phenomenon to differentiate the present molecular framework from previous others. DFT computational study presented the relative stability of individual orientatiomers. This discovery would be anticipated to result in a new stereochemistry branch and to have a broad impact on chemical, biomedical, and material sciences in the future.